DATA PROTECTION IN THE EU - Kmetyk, Khrystyna V. (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2019)
Purpose: to research the processing by an individual, a company or an organization of personal data relating to individuals in the EU. Methods: documentary analysis and synthesis, comparative analysis, objective truth, cognitive-analytical, etc. Results: an author made a conclusion that the EU General Data Protection Regulation is an essential step to strengthen individuals’ fundamental rights in the digital age and facilitate business by clarifying rules for companies and public bodies in the digital single market. A single law will also do away with the current fragmentation in different national systems and unnecessary administrative burdens. Discussion: clarified main rules of the EU General Data Protection Regulation as an essential step to strengthen individuals’ fundamental rights in the digital age and facilitate business.